The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/cncr.31370
|View full text |Cite
|
Sign up to set email alerts
|

Results of second salvage therapy in 673 adults with acute myelogenous leukemia treated at a single institution since 2000

Abstract: This large-scale analysis establishes the modern historic results of second salvage therapy in AML and validates the prognostic models associated with outcome. These data could be used to analyze the differential benefits of current or future investigational strategies under evaluation in this setting and for the purpose of potential approval of new agents in the United States and the world. Cancer 2018;124:2534-40. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…Our interpretation of the effect of treatment on disease free survival and OS was limited by the small sample size estimates and short follow-up time. Nevertheless, the survival data in our study compared favorably to historical OS estimates of 5.9 and 4.7 months in first- and second- salvage AML, respectively ( 54 , 55 ). In this context, survival in R/R AML is highly influenced by the post-remission therapy, ASCT being the only consistently curative option with patients rarely achieving durable remissions with non-transplant strategies ( 56 ).…”
Section: Discussionsupporting
confidence: 54%
“…Our interpretation of the effect of treatment on disease free survival and OS was limited by the small sample size estimates and short follow-up time. Nevertheless, the survival data in our study compared favorably to historical OS estimates of 5.9 and 4.7 months in first- and second- salvage AML, respectively ( 54 , 55 ). In this context, survival in R/R AML is highly influenced by the post-remission therapy, ASCT being the only consistently curative option with patients rarely achieving durable remissions with non-transplant strategies ( 56 ).…”
Section: Discussionsupporting
confidence: 54%
“…This is comparable to the 19% CR/CRi observed with single-agent venetoclax [60]. Hence, with the data available, the value of venetoclax as a salvage therapy either alone or in combination with HMAs/LDAC appears comparable with standard salvage regimens [77].…”
Section: Targeting Bcl-2 In Amlsupporting
confidence: 52%
“…In general, however repetition at relapse of the same induction and post‐remission therapy used initially leads to worse results This suggests that even should second CR be attained with standard induction, post‐remission therapy should, if feasible, include allo HCT, particularly if this has not been done before; indeed, regardless of prognostic group patients lived longer if in CR2 they received allo HCT, although, as usual, various selection biases may have affected the decision to perform allo HCT 150 . The recommendation for new therapy/clinical trials in all patients in the intermediate and, particularly worst, Breems et al prognostic groups certainly extends to older patients, who all else being equal would be expected to do even worse than the patients analyzed by Breems et al 151 and to all patients who are receiving a second re‐induction attempt after failing a first 152 …”
Section: Relapsed and Refractory Amlmentioning
confidence: 99%
“…Uproleselan disrupts adherence, putatively re‐sensitizing blasts to chemotherapy. A single‐arm trial of uproleselan added to MEC reported 156 a 45% CR/CRi rate and 12.8 month median survival in the 22 patients with >10% E‐selectin ligand expression vs 29% CR/CRi rate with 5.4 month median survival in the 14 patients with less expression; 79% of the former and 72% of the latter patients were in the Breems et al poor prognostic group or receiving at least second salvage suggesting results in the higher expression group were better than those otherwise expected 150,152 . A randomized trial comparing FAI or MEC +/− uproleselan is ongoing in relapsed/ refractory and newly‐diagnosed patients.…”
Section: Relapsed and Refractory Amlmentioning
confidence: 99%